Climate Change as a Business Risk: An Indonesian Banking Industry Perspective - Puspitasari, Indah; Faturohman, Taufiq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Climate change has emerged as a new business risk that must be carefully evaluated, forecasted, mitigated and managed by all corporate organizations, including banks. Climate change has a profound effect on finance and business continuity, so all sectors, including the financial industry, must plan for it. In June 2022, the Basel Committee on Banking Supervision (BAS) announced general principles for banks around the world to manage and supervise climate change risks, entitled “Principles for the Effective Management and Supervision of Climate-Related Financial Risks”. Managing Climate-Related Financial Risks requires an acceptable management structure and information tools that can be used by banks to monitor, measure and manage asset portfolios affected by Climate-Related Financial Risks. In addition, this research also aims to assess the readiness of Indonesian banks in implementing an effective BCBS management framework for climate change-related financial risks. This research utilizes a qualitative research type. The research methodology used in this study is to use in-depth and semi-structured interviews to obtain narratives and subjective reflections from the participants. The main purpose of the interviews was to uncover significant meanings and structures inherent in their professional experiences. By using a sample method involving regulators and selecting banking executives who specialize in risk management. The results of this study provide an explanation of the perspective of Indonesian banks in dealing with business risks due to climate change, OJK's policies related to banking risk management due to climate change, OJK's response to the possibility of adopting an effective management framework for financial risks related to climate change developed by the BCBS in terms of, Bank Indonesia's Perspective on the Integration of Climate Risk into Macro Prudential Supervision, Impact on Financial Stability and Economic Resilience, and Policy Recommendations, and Banks' readiness to implement an effective financial risk management framework for financial risks related to climate change based on the risk management framework developed by the Basel Committee on Banking Supervision (BCBS).